The last beach - Pilkey, Orrin H., 1934-; Cooper, J. A. G. (Duke University Press, 2014)
The geologists Orrin H. Pilkey and J. Andrew G. Cooper sound the alarm in this frank assessment of our current relationship with beaches and the grim future if we do not change the way we understand and treat our irreplaceable shores.